Regulation of sigma B levels and activity in Bacillus subtilis. - Benson, A K (1993)
The sigB operon of Bacillus subtilis encodes sigma B plus three additional proteins (RsbV, RsbW, and RsbX) that regulate sigma B activity. Using an anti-sigma B monoclonal antibody to monitor the levels of sigma B protein, PSPAC to control the expression of the sigB operon, and a ctc-lacZ reporter system to monitor sigma B activity, we observed that the rsbV and rsbW products control sigma B activity at the ctc promoter independently of their effects on sigma B levels. In contrast, RsbX was found to have no effect on expression of ctc when the sigB operon was controlled by PSPAC. The data are consistent with RsbV and RsbW being regulators of sigma B activity and RsbX acting primarily as a negative regulator of sigB operon expression. Evidence that stationary-phase induction of the sigma B-dependent ctc promoter is accomplished by a reduction in RsbW-dependent inhibition of sigma B activity is also presented. In addition, Western blot (immunoblot) analyses of sigB operon expression demonstrated that sigma B accumulation is coupled to the synthesis of its primary inhibitor (RsbW). This finding is consistent with RsbW and sigma B being present within the cell in equivalent amounts, a circumstance that would permit RsbW to directly influence sigma B activity by a direct protein-protein interaction.